2019
DOI: 10.1111/jedm.12203
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Targeted Multistage Calibration Designs Under Practical Constraints: A Simulation Study

Abstract: Calibration of an item bank for computer adaptive testing requires substantial resources. In this study, we investigated whether the efficiency of calibration under the Rasch model could be enhanced by improving the match between item difficulty and student ability. We introduced targeted multistage calibration designs, a design type that considers ability-related background variables and performance for assigning students to suitable items. Furthermore, we investigated whether uncertainty about item difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Several studies have investigated the accuracy with which experts, such as test developers, content experts, or item authors, can rate item difficulty, and they have found moderate to high correlations between ratings and empirical item difficulties (e.g., Bejar, 1983;Hambleton and Jirka, 2006;Sydorenko, 2011;Wauters et al, 2012). We conclude from these findings and from our own practical experiences that the distribution of items across modules of different target difficulties can deviate in a practical setting from the optimal distribution observed in a theoretical setting, where the difficulty of all items is known in advance (see also Berger et al, 2019).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Several studies have investigated the accuracy with which experts, such as test developers, content experts, or item authors, can rate item difficulty, and they have found moderate to high correlations between ratings and empirical item difficulties (e.g., Bejar, 1983;Hambleton and Jirka, 2006;Sydorenko, 2011;Wauters et al, 2012). We conclude from these findings and from our own practical experiences that the distribution of items across modules of different target difficulties can deviate in a practical setting from the optimal distribution observed in a theoretical setting, where the difficulty of all items is known in advance (see also Berger et al, 2019).…”
Section: Introductionmentioning
confidence: 59%
“…Instead of empirical item parameters, they have to rely on expert judgments, which might be biased (e.g., Bejar, 1983;Hambleton and Jirka, 2006;Sydorenko, 2011;Wauters et al, 2012). As a consequence, the new items might end up in a non-optimal test module, which can, in turn, result in biased parameter estimates (Berger et al, 2019).…”
Section: Practical Constraints In Developing Optimal Multistage Testmentioning
confidence: 99%
See 3 more Smart Citations